Wall shear stress from jetting cavitation bubbles: influence of the stand-off distance and liquid viscosity - Zeng, Qingyun (2022)
We study systematically the cavitation-induced wall shear stress on rigid boundaries as a function of liquid viscosity and stand-off distance using axisymmetric volume of fluid (VoF) simulations. Here, is defined with the initial distance of bubble centre from the wall and the bubble equivalent radius at its maximum expansion. The simulations predict accurately the overall bubble dynamics and the time-dependent liquid film thickness between the bubble and the wall prior to the collapse. The spatial and temporal wall shear stress is discussed in detail as a function of and the inverse Reynolds number. The amplitude of the wall shear stress is investigated over a large parameter space of viscosity and stand-off distance. The inward stress is caused by the shrinking bubble and its maximum value follows (kPa) for <![CDATA[$0.5<\gamma. The expanding bubble and jet spreading on the boundary produce an outward-directed stress. The maximum outward stress is generated shortly after impact of the jet during the early spreading. We find two scaling laws for the maximum outward stress with for and for, where is the jet impact velocity and is the distance between lower bubble interface and wall prior to impact.